The T‐Type Calcium Channel CACNA1H is Required for Smooth Muscle Cytoskeletal Organization During Tracheal Tubulogenesis - Ziying Liu; Chunyan Lu; Li Ma; Changjiang Li; Haiyun Luo; Yiqi Liu; Xinyuan Liu; Haiqing Li; Yachao Cui; Jiahang Zeng; Natalia Bottasso‐Arias; Debora Sinner; et al. (Advanced Science)
Abstract Abnormalities of tracheal smooth muscle (SM) formation are associated with several clinical disorders including tracheal stenosis and tracheomalacia. However, the cellular and molecular mechanisms underlying tracheal SM formation remain poorly understood. Here, it is shown that the T‐type calcium channel CACNA1H is a novel regulator of tracheal SM formation and contraction. Cacna1h in an ethylnitrosourea forward genetic screen for regulators of respiratory disease using the mouse as a model is identified. Cacna1h mutants exhibit tracheal stenosis, disorganized SM and compromised tracheal contraction. CACNA1H is essential to maintain actin polymerization, which is required for tracheal SM organization and tube formation. This process appears to be partially mediated through activation of the actin regulator RhoA, as pharmacological increase of RhoA activity ameliorates the Cacna1h‐mutant trachea phenotypes. Analysis of human tracheal tissues indicates that a decrease in CACNA1H protein levels is associated with congenital tracheostenosis. These results provide insight into the role for the T‐type calcium channel in cytoskeletal organization and SM formation during tracheal tube formation and suggest novel targets for congenital tracheostenosis intervention.